Strategi Pemasaran Syariah Dalam Meningkatkan Daya Saing UMKM Kerupuk Di Surabaya - Tate Agape Bawana (Program Studi Perbankan Syariah STAI Al-Fitrah Surabaya, 2023)
Marketing strategy can be seen as one of the basics used in planning a company or factory as a whole. In marketing activities, we often encounter people who cheat and fraud occurs, but if we apply the Islamic system in marketing then things like that will not happen. Basically, for Muslims the Prophet Muhammad SAW has taught us how to use an Islamic marketing system. However, because society has relied on the conventional marketing system, the sharia marketing system is less well known. This study aims to get an overview of the marketing strategy to increase competitiveness, and to find out how effective the implementation of the marketing strategy has been. This type of research is qualitative, this research was carried out in the Kerupuk UMKM, Kenjeran Village. Data collection techniques with documentation and interviews. The results of the analysis of the effectiveness of marketing strategies show an increase in sales from month to month and have experienced a decline in sales, this can be used as a reference for the effectiveness of marketing strategies in competition between cracker factories.